Characteristics of intestinal microbiota in infants with late-onset breast milk jaundice - Guo, Qianying; Liu, Xinran; Cui, Mingxuan; Li, Xuening; Yang, Chen; Zhao, Shilong; Pan, Lina; Peng, Xiaoyu; Wang, Linlin; Liu, Peng (Frontiers in Nutrition, 2023)
In this paper, microbiota analysis was determined to analyze the structure and difference of intestinal microbiota between LBMJ (late-onset breast milk jaundice) infants and healthy individuals. We collected fresh fecal samples from 13 infants with LBMJ and 13 healthy individuals, then determined the intestinal microbiota by 16s rRNA sequencing. The differences of microbiota structure, diversity and functional characteristics between the two groups were analyzed, and the correlation between dominant genus and TcB (transcutaneous bilirubin) value was calculated. In this study, there were no significant differences in maternal demographic characteristics, neonatal status and macronutrients in breast milk between the two groups (P > 0.05). There are differences in the structure of intestinal microbiota between LBMJ and the control group. At the genus level, the relative abundance of Klebsiella in the case group is high (P < 0.05). At the same time, correlation analysis indicates that the abundance of Klebsiella is positively correlated with TcB value. The intestinal microbiota richness and diversity (Alpha diversity and Beta diversity) of the two groups were significantly different (P < 0.05). LEfSe analysis showed that 25 genera including Klebsiella was significantly enriched in the LBMJ infants, and the other 17 species are enriched in the control group. Functional prediction analysis indicated that 42 metabolic pathways may be related to the occurrence of LBMJ. In conclusion, characteristic changes are seen in intestinal microbiota compositions between LBMJ infants and the healthy controls. Klebsiella is closely associated with the severity of the disease, which may be due to enhanced β-glucuronidase activity.